2021
DOI: 10.1016/j.pcd.2020.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Indirect comparison of efficacy and safety of insulin glargine/lixisenatide and insulin degludec/insulin aspart in type 2 diabetes patients not controlled on basal insulin

Abstract: Background: Fixed-dose combinations of insulin glargine/lixisenatide (IGlarLixi) or insulin degludec/insulin aspart (IDegAsp) constitute treatment intensification in type 2 diabetes mellitus (T2D). Objectives: Compare efficacy and safety of IGlarLixi and IDegAsp (as intensification from basal insulin), by indirect comparison of phase III trials, in the absence of head-to-head trials. Study eligibility criteria: Studies comparing treatment intensification by once-daily IDegAsp or IGlarLixi to basal insulin. Dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Because of the absence of a Japanese IDegAsp prior insulin study and the small number of studies overall, we were not convinced of the merits of separate analyses of prior insulin versus no prior insulin, but a very recent publication selected the two international prior insulin studies we identified 3 , 16 and reported, by ITC, statistically significant HbA1c and bodyweight improvements of the same order we found, in addition to improvements in PPPG. 29 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the absence of a Japanese IDegAsp prior insulin study and the small number of studies overall, we were not convinced of the merits of separate analyses of prior insulin versus no prior insulin, but a very recent publication selected the two international prior insulin studies we identified 3 , 16 and reported, by ITC, statistically significant HbA1c and bodyweight improvements of the same order we found, in addition to improvements in PPPG. 29 …”
Section: Discussionmentioning
confidence: 99%
“…Because of the absence of a Japanese IDegAsp prior insulin study and the small number of studies overall, we were not convinced of the merits of separate analyses of prior insulin versus no prior insulin, but a very recent publication selected the two international prior insulin studies we identified 3,16 and reported, by ITC, statistically significant HbA1c and bodyweight improvements of the same order we found, in addition to improvements in PPPG. 29 One issue might be that iGlar doses were capped in the iGlarLixi studies but not in the IDegAsp studies, thus possibly giving a comparator advantage to iGlarLixi. However, this issue has been investigated for some of the LixiLan studies by Schmider et al, who reported that uncapping the iGlar dose would not have led to significant improvements in fasting self-monitored blood glucose or HbA1c.…”
Section: Safetymentioning
confidence: 99%